การพัฒนาซอฟท์แวร์เพื่อหาพารามิเตอร์ ของแรงดันทดสอบอิมพัลส์รูปคลื่นฟ้าผ่า - ศรณรงค์ สุวรรณธนารักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Presents an algorithm for analyzing parameters of full and chopped (on front) lightning impulse voltage, obtained from a digital oscilloscope, according to IEC 60-1 standard. Theory used to write a mean curve is "Nonlinear least square curve fitting method". There are some techniques used to write this mean curve. For full wave, we divide curve fitting procedure into two stage- the first stage is tail wave part fitting, and the second one is front wave part fitting. To write a mean curve for chopped (on front) wave, technique applied is keeping some model function parameters fixed. The algorithm developed as presented before is evolved into a software and tested with IEC 1083-2 standard. The result shows that the developed software can analyze parameters of reference waveform in case 1, 2, 3, 4, 6, 7, 11, 12 and 13 correctly corresponding to the standard. In the case of reference waveforms in case 3 and 8, we can improve by adjusting the base value finding procedure which occur before the normalization, adjusting the parameters of S.G. filter suitably, and adjusting the origin finding procedure which used to write a mean curve. Because the reference waveform case 14 is a measured one, the parameters judgement criteria used by the standard composer may differ from the one used in this thesis.